Characterizing a rare neurogenetic disease, SLC13A5 citrate transporter disorder, utilizing clinical data in a cloud-based medical record collection system - Spelbrink, Emily M.; Brown, Tanya L.; Brimble, Elise; Blanco, Kirsten A.; Nye, Kimberly L.; Porter, Brenda E. (Frontiers in Genetics, 2023)
SLC13A5 Citrate Transporter Disorder is a rare autosomal recessive genetic disease that has a constellation of neurologic symptoms. To better characterize the neurologic and clinical laboratory phenotype, we utilized patient medical records collected by Ciitizen, an Invitae company, with support from the TESS Research Foundation. The 15 patients reported here had a suspected genetic diagnosis of SLC13A5 Citrate Transporter Disorder, all had epilepsy, and global developmental delay. Patients continued to attain motor milestones, though much later than their typically developing peers. Clinical diagnoses support abnormalities in communication, and low or mixed tone with several movement disorders, including, ataxia and dystonia. Serum citrate was elevated in the 3 patients in whom it was measured; other routine laboratory studies assessing renal, liver and blood function had normal values or no consistent abnormalities. Many electroencephalograms (EEGs), 1 to 35 per patient, were performed, and most but not all were abnormal, with slowing and/or epileptiform activity. Fourteen of the patients had one or more brain magnetic resonance imaging (MRI) reports, 7 patients had at least one normal brain MRI, but not with any consistent findings except white matter signal changes. These results show that in addition to the epilepsy phenotype, SLC13A5 Citrate Transporter Disorder impacts development, with marked abnormalities in motor, tone, coordination, and communication skills. Further, utilizing cloud-based medical records allows industry, academic, and patient advocacy group collaboration to provide preliminary characterization of a rare genetic disorder. Further characterization of the neurologic phenotype will be critical to future study and developing treatment for this and related rare genetic disorders.